A Complex Triad in Law: Moral, Pedagogy and Link with other Sciences - Gudiño Flores, Cynthia Mishel (2017)
The material Constitution can be understood as the daily dynami. The traditional idea about Law as a pure autonomous and delimited system of other areas of knowledge, and the lack of innovation in the way of teaching it, have serious negative consequences on the knowledge and thinking of Law students, therefore in jurists. In order to develop a new teaching model to help to correct all the shortcomings of the traditional model and ensure the achievement of appropriate and practical knowledge of Law and the sciences with it is constantly related; this essay is carry out based on a thorough investigation that allows analyzing the incidence of morality, teaching style and the linking of Law with other sciences. Considering Law as a dynamic and versatile system, it is known that it needs to be linked to other areas of knowledge and that it is influenced by the most innate human principles. KEYWORDS: lack of innovation, incidence, linking, practical, morality. JEL CODE: A14